Intima-Media Thickness in Women with the History of Hypertensive Disorders of Pregnancy as a Risk Marker of the Occurrence of Cardiovascular Pathology in Advanced Reproductive and Perimenopausal Age - Davydova, Iuliia V.; Kryvorchuk, Ihor G.; Siromakha, Sergii O.; Lymanska, Alisa Yu.; Kravets, Olga M. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Over the past twenty years, it has been proven that a history of preeclampsia entails a 4-fold risk of hypertension, coronary heart disease, stroke, type 2 diabetes, metabolic syndrome in the affected women at the age of 50-55 years. Evaluation of intima-media thickness (IMT) has diagnostic value for the assessment of remodeling and atherosclerotic vascular lesions and practical importance as a predictor of vascular accidents in patients with hypertension and atherosclerosis. The aim. To evaluate the IMT as an integrative biomarker of the occurrence of cardiovascular pathology in women with hypertensive disorders of pregnancy in their advanced reproductive age and in perimenopausal age. Materials and methods. We studied 51 women at the age of 48-55 years with the history of severe preeclampsia. The women were asked to fill out a questionnaire in which they indicated the presence of a diagnosis of hypertension, angina pectoris at the time of filling the questionnaire. The diagnosis of hypertension and angina attacks as well as other descriptions of the disease were taken away from the results of the women’s questionnaire. The investigators were not given copies of medical records. The control group consisted of 20 women aged 48-55 who had no history of preeclampsia or any other hypertensive disorders of pregnancy. Ultrasound imaging of the carotid arteries was performed according to the recommendations of the American Society of Echocardiography 2020 in women of both groups using SonoAce-8000 Ex scanner (Medison, South Korea) with a linear sensor UST5524 with a frequency of 7 MHz. IMT less than 0.7 mm was taken as a normal value for women. Results. It was revealed that almost every fourth woman at the age of 48-55 with the history of preeclampsia had signs of early angina attacks, and 30% suffered from hypertension. A threatening fact is that almost 6% of women at the age of 48-55 had the history of vascular thrombosis which is a manifestation of early atherosclerotic vascular lesions in the group of women with gestational hypertensive disorders. It is noteworthy that 21 (41.2%) women with the history of severe preeclampsia felt healthy and did not have any complaints. Importantly, among the women surveyed who had no health complaints, 66.6% (14 of 21) had IMT 0.85±0.01 mm. This accounts for about one third (27.4%) among 51 patients. This category of women is at high risk of developing cardiovascular complications in the future and require further monitoring and detailed examination. Thrombotic complications (dynamic bowel obstruction, mesenteric vascular thrombosis) were observed in 3 (5.9 %) women at the age of 48-55 with the history of severe preeclampsia. Conclusions. Examinations of women with the history of preeclampsia revealed that women at the age of 48-55 had increased IMT. It should be noted that increased IMT was found both in women with cardiovascular pathology (hypertension, thrombosis, angina attacks) and in asymptomatic patients. Taking into account that increased IMT is one of the characteristics of target organ damage in patients with hypertension and the marker of cardiovascular events in asymptomatic patients, it is important to include this examination in follow-up for women with the history of severe preeclampsia in order to avoid the development of early severe cardiovascular pathologies.